Algebra:

1. (a + b) = a + 2ab + b

2. (a – b) = a – 2ab + b

3. (a + b) (a – b) = a – b

4. (x + a)(x + b) = x + (a + b)x + ab

5. (x + a)(x – b) = x + (a – b)x – ab

6. (x – a)(x + b) = x + (b – a)x – ab

7. (x – a)(x – b) = x – (a + b)x + ab

8. (a + b) = a + b + 3ab(a + b)

9. (a – b) = a – b – 3ab(a – b)

10. (x + y + z) = x + y + z + 2xy +

2yz + 2xz

11. (x + y – z) = x + y + z + 2xy

– 2yz – 2xz

12. (x – y + z) = x + y + z – 2xy –

2yz + 2xz

13. (x – y – z) = x + y + z – 2xy

+ 2yz – 2xz

14. x + y + z – 3xyz = (x + y + z)(x

+ y + z – xy – yz -xz)

15. (x + a) (x + b) (x + c) = x + (a + b

+c)x + (ab + bc + ca)x + abc

16. x + y = (x + y) (x – xy + y )

17. x – y = (x – y) (x + xy + y )